TB LAMP assay, a beneficial tool for the diagnosis of Tubercular meningitis in resource-limited settings - Vineeta Mittal; Manoj Kumar; Ajay Kumar Singh (Journal of Infection in Developing Countries)
Introduction: Tubercular meningitis (TBM) is a serious public health problem in developing countries as it leads to significant mortality and residual neurological sequelae. The estimated mortality due to TBM in India is 1.5 per 100,000 population. In resource-limited settings, only the Ziehl-Neelsen (ZN) stain, which has very little sensitivity, is available. The World Health Organization recommended the Loop Mediated Isothermal Amplification (TB LAMP) assay for pulmonary tuberculosis only. We evaluated this test for tubercular meningitis as well.